2004
DOI: 10.1002/ptr.1430
|View full text |Cite
|
Sign up to set email alerts
|

Extracts from St John's wort and their antimicrobial activity

Abstract: In an effort to carry out a more in-depth investigation on the antimicrobial properties of H. perforatum, we have assayed different extracts (MeOH; petroleum ether; CHCl(3) and EtOAc) from the aerial parts of the plant against selected microorganisms. Growth inhibition was observed only for Gram-positive bacteria, B. subtilis and B. cereus being the most susceptible to the tested drugs. The Hypericum extract obtained with EtOAc was the most active. The main constituents of this extract, as determined by HPLC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 13 publications
(16 reference statements)
1
63
0
2
Order By: Relevance
“…On the other hand, Al-Khayat and Blank (1985) reported the antimicrobial action of aqueous clove extract against Bacillus subtilis. Avato, Raffo, Guglielmi, Vitali, & Rosato, 2004) reported that the ethyl acetate extract of St. John's Wort that contained hypericin and hyperforin had inhibitory effects on Bacillus cereus and B. subtilis.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Al-Khayat and Blank (1985) reported the antimicrobial action of aqueous clove extract against Bacillus subtilis. Avato, Raffo, Guglielmi, Vitali, & Rosato, 2004) reported that the ethyl acetate extract of St. John's Wort that contained hypericin and hyperforin had inhibitory effects on Bacillus cereus and B. subtilis.…”
Section: Discussionmentioning
confidence: 98%
“…Results of those studies have revealed that extract of Hypericum exert several pharmacological properties including antidepressant, antimicrobial and wound healing effects (Ishiguro et al 1990;Decosterd et al 1991;Jayasuriyab et al 1991;Rocha et al 1995;Ö ztürk et al 1996;Sokmen et al 1999;Daudt et al 2000;Mukherjee et al 2000;Pistelli et al 2000;Avato et al 2004). …”
Section: Introductionmentioning
confidence: 98%
“…It is currently among the most popular drugs against mild depression in complementary medicine. In addition to its potent photo-damaging effects on cancer cells [26], several studies indicated that HYP is active against various Gram-positive bacteria [27][28][29].…”
Section: Introductionmentioning
confidence: 99%